First detection and characterization of macrolide-resistant Mycoplasma pneumoniae strains in Cuba. (March 2019) - Rodriguez, Nadia; Mondeja, Brian; Sardiñas, Ruxana; Vega, Dania; Dumke, Roger
Abstract: Objectives: Mycoplasma pneumoniae is a common cause of community-acquired pneumonia in humans. Treatment of infections can be complicated by the occurrence of macrolide resistant strains. The study was conducted to evaluate the presence of resistant strains in Cuba and to determine the corresponding genotypes. Methods: DNA of M. pneumoniae isolates and positive respiratory tract specimens collected in the years 2012 and 2017 were tested for resistance-associated mutations of 23S rRNA. In addition, strain types (P1 and MLVA) were determined. Results: Macrolide resistance mutations were confirmed in 5 out of 27 strains (18.5%). Whereas both P1 subtypes 1 and 2 as well variants V2a and V2c were identified, only two MLVA types (4/5/7/2 and 3/5/6/2) could be found. Conclusions: During both sampling years, circulation of macrolide resistant strains was demonstrated. No association of resistance with a particular P1/MLVA type was found. Future longitudinal sampling to monitor prevalence of macrolide resistance of M. pneumoniae is recommended to verify the resistance pattern of this important pathogen of human respiratory tract infections.